Partially Coherent Dual and Quad Airy‐Like Beams. Issue 4 (15th February 2021) - Pan, Keming; Xu, Jia; Zhang, Yao; Zhao, Daomu
Abstract: Partially coherent multi‐Airy‐like beams are investigated by introducing coordinate transformation parameters and combining them with the theory of multi‐beam superposition under symmetrical conditions, for the case of dual and quad as examples. The accurate propagation position of the mutual‐focusing point is obtained by analyzing the normalized spectral density (SD) curves at different planes. The outcomes show that both the optical frame and the interference pattern can be changed by means of adjusting the coordinate transformation parameters. For a special circumstance, the transverse SD overlapping profile is presented in a rotational four‐square grid. In addition, the coordinate transformation parameters periodically affect the distance between the two main lobes, which provides us a new idea with adjusting the width of the optical frame edges. Moreover, both the peak intensity of the SD and the divergence speed can be controlled by tuning the value of the equivalent beam width. These results may provide new inspiration for applications of partially coherent Airy‐like beams in optical propagation, capture, and communication. Abstract : The partially coherent dual and quad Airy‐like beams are investigated by introducing the coordinate transformation parameters and combining with the theory of multi‐beams superposition. Both the optical frame and the interference pattern can be changed by adjusting the coordinate transformation parameters. Moreover, the peak of the spectral density and the divergence speed are controlled by the equivalent beam width.